2009
DOI: 10.1556/aphysiol.96.2009.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term 50 Hz electromagnetic field exposure on the behavior of rats

Abstract: Extremely low-frequency electromagnetic field generated by transformer stations located within buildings has been suspected to initiate non-specific health problems. This possibility was examined in model experiments in rats. Following short-term exposure (50 Hz, 500 mircoT, 20 min), situational and social anxiety as well as locomotor activity pattern were examined by several different tests (elevated plus-maze, novel object exploration, social interaction and territoriality).Based on our results having obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Results revealed that the EMF group had lowest total distance traveled and movement velocity in the Open field test. These results are in line with previous studies (Balassa et al, 2009b;Balind et al, 2014b;Janać et al, 2012b), that assessed that 48 h of exposure to 50 Hz low-frequency EMF on the motor activity of insects. They concluded that their motor activity was reduced (Balind et al, 2014b).…”
Section: Open-field Testsupporting
confidence: 93%
“…Results revealed that the EMF group had lowest total distance traveled and movement velocity in the Open field test. These results are in line with previous studies (Balassa et al, 2009b;Balind et al, 2014b;Janać et al, 2012b), that assessed that 48 h of exposure to 50 Hz low-frequency EMF on the motor activity of insects. They concluded that their motor activity was reduced (Balind et al, 2014b).…”
Section: Open-field Testsupporting
confidence: 93%
“…364 B. Jana ć et al (Rudolph et al 1985, Choleris et al 2001, Del Seppia et al 2003, Pe š ic´ et al 2004, Janac´ et al 2005, Shin et al 2007, Whissell and Persinger 2007, Balassa et al 2009). Our results are consistent with these data and confi rm once again the ability of ELF-MF to modulate diff erent steps of synaptic transmission in the brain structures involved in control of motor behavior.…”
Section: Behavioral Eff Ects Of Elf-mf In 10-month-old Gerbilsmentioning
confidence: 99%
“…Several neurotransmitter systems such as dopamine (DA), glutamate (Glu), acetylcholine (ACh), serotonin (5-HT), and gamma-aminobutyric acid (GABA) take part in this process, and their interactions contribute the regulation of animal movement (Di Chiara et al 1994, Nakano et al 2000, Esposito 2006, Mora et al 2008). Literature data have shown that ELF-MF alone or in combination with a neuroactive agent can aff ect, among other things, motor behavior of experimental animals (Davis et al 1984, Rudolph et al 1985, Trzeciak et al 1993, Sienkiewicz et al 1994, Choleris et al 2001, Del Seppia et al 2003, Pe š i c´ et al 2004, Shupak et al 2004, Janać et al 2005, Shin et al 2007, Whissell and Persinger 2007, Balassa et al 2009. Th e results are contradictory and dependent on characteristics of the applied magnetic fi eld (type, frequency, intensity and exposure duration) and of a living organism (age, sex, species, functional state).…”
Section: Introductionmentioning
confidence: 99%
“…Triggers of diffuse hair loss are mainly composed of physiologic or emotional stresses, nutritional deficiencies and endocrine imbalances (Harrison & Bergfeld, 2009). Balassa, Szemerszky, & Bárdos (2009) reported that 50 Hz, 500 mT EMF may induce some discomfort and increase situational anxiety. Therefore, the discomfort and situational anxiety may have some effects on the loss of hair.…”
Section: Effects Of Elf-emf On Nervous Systemmentioning
confidence: 99%